A quick assessment tool for human‐directed aggression in pet dogs. Issue 2 (14th August 2013) - Klausz, Barbara; Kis, Anna; Persa, Eszter; Miklósi, Ádám; Gácsi, Márta
<x xml:space="preserve">Abstract</x> Many test series have been developed to assess dog temperament and aggressive behavior, but most of them have been criticized for their relatively low predictive validity or being too long, stressful, and/or problematic to carry out. We aimed to develop a short and effective series of tests that corresponds with (a) the dog's bite history, and (b) owner evaluation of the dog's aggressive tendencies. Seventy‐three pet dogs were divided into three groups by their biting history; non‐biter, bit once, and multiple biter. All dogs were exposed to a short test series modeling five real‐life situations: friendly greeting, take away bone, threatening approach, tug‐of‐war, and roll over. We found strong correlations between the in‐test behavior and owner reports of dogs' aggressive tendencies towards strangers; however, the test results did not mirror the reported owner‐directed aggressive tendencies. Three test situations (friendly greeting, take‐away bone, threatening approach) proved to be effective in evoking specific behavioral differences according to dog biting history. Non‐biters differed from biters, and there were also specific differences related to aggression and fear between the two biter groups. When a subsample of dogs was retested, the test revealed consistent results over time. We suggest that our test is adequate for a quick, general assessment of human‐directed aggression in dogs, particularly to evaluate their tendency for aggressive behaviors towards strangers. Identifying important behavioral indicators of aggressive tendencies, this test can serve as a useful tool to study the genetic or neural correlates of human‐directed aggression in dogs. Aggr. Behav. 40:178–188, 2014. © 2013 Wiley Periodicals, Inc.